The Continuity of Limas House of Pangeran Syarif Ali in South Sumatra from Dutch to Present - Wargadalem, Farida Ratu; Dewantara, Bima Pranata (Yupa: Historical Studies Journal, 2024)
This article aims to discover the process of changing ownership and moving locations, as well as trace the process of development and subsequent changes in Rumah Limas in the South Sumatra State Museum environment. The method used is the historical method which consists of four stages, namely: heuristics, source criticism, interpretation, and historiography. The results showed that this Limas House had changed ownership and places six times. At the beginning of its construction, this house was located inside the Kuto Besak Palace, then moved by the Dutch Colonial Government to near the Sekanak River, then moved again outside Palembang City (Marga Batun and Pemulutan) and finally returned to Palembang (behind the Palembang Gemeente Office). In 1933, the Dutch made this Limas House as a Gemeente Museum until the entry of Japan into Palembang. After independence, this house was used as the Bari Museum Palembang, then due to construction reasons this house was moved again to the neighborhood of the South Sumatra State Museum (Balaputra Dewa) and stayed until now.